Perbandingan Pemberian Fermentasi Beras Merah (Oryza sativa) dan Fermentasi Beras Hitam (Oryza sativa L. indica) terhadap Tekanan Darah Sistole Ibu Hamil dengan Preeklamsia - Khoerunnisa, Asma Alfiah; Muhammad Muayyad Billah (Sultan Agung Islamic University of Semarang, 2025)
Preeclampsia is a hypertensive disorder of pregnancy that causes 75% of the most direct causes of maternal death. One way to reduce the risk of preeclampsia is with complementary therapy using fermentation in brown rice and black rice that produce natural lovastatin. This natural product is a traditional method that can provide additional benefits to health. The purpose of this study is to compare and analyze the effect of administration between brown rice fermentation (oryza sativa) and black rice fermentation (oryza sativa l. indica) on pregnant women with preeclampsia in the working area of TPMB Tuty, Mekarmukti Village, West Bandung Regency in 2025. The research method uses was true experimental with the randomized pretest and posttest control group design. The study will be carried out on 24 pregnant women with preeclampsia in the work area of TPMB Tuty, Mekarmukti Village, West Bandung Regency, in 2025. Sampling was done using simple random sampling in three groups, namely the red rice fermentation group, the black rice fermentation group, and the control group. The number of samples was 8 respondents in the experimental group using fermented brown rice, 8 respondents in the experimental group using black rice fermentation and 8 respondents in the control group using orange juice. Each group received 5 cc per day for fourteen days. Data analysis using the T-test. The results of the study after the fourteen-day intervention showed that there was a significant comparison of brown rice fermentation and black rice fermentation (p=0.041). The average blood pressure of the mother's systole after being given fermented brown rice was 144.63 mmHg and the average blood pressure of the mother's systole after being given black rice fermentation was 142.75 mmHg.